Pain informed movement compared to neuromuscular exercise and standard education in people with knee osteoarthritis: A pilot and feasibility randomized controlled trial - Lisa C. Carlesso; Shirin Modarresi; Neil Pearson; Kim Madden; Margaret Fahnestock; Kim L. Bennell; Tuhina Neogi; Erfan Shafiee (Osteoarthritis and Cartilage Open, 2025)
Objective: To determine the feasibility of conducting a full-scale randomized controlled trial to test the effectiveness of pain informed movement (PIM) (includes mind-body techniques, neuromuscular strengthening exercises (NEMEX) and pain neuroscience education), compared to NEMEX and standard education in people with knee osteoarthritis (KOA). Methods: Adults ≥40 years with KOA were randomized to a twice weekly in-person group program for 8 weeks. Education was delivered through weekly videos. Recruitment, follow-up, adherence (attendance), compliance to home exercises, burden of procedures as well as patient-reported clinical outcomes, quantitative sensory tests, the sit to stand test, and serum levels of brain derived neurotrophic factor and nerve growth factor were assessed before and immediately after treatment. Focus groups were conducted post intervention. Results: 210 people were screened for eligibility. 69 (33 ​%) were randomized and 59 (28 PIM, 31 NEMEX; 86 ​%) completed the trial. The primary outcome of follow up rate was met along with all other a priori criteria. There was high acceptability of both interventions (≥86 ​%), and perceived low burden of procedures (≥80 ​%). Only minor adverse events were reported. Secondary outcomes improved across most clinical measures in both groups with the PIM group showing clinically important improvement in pain. Focus group feedback suggests the need to consider an alternative format to video delivery of the education content. Conclusion: This pilot RCT indicates that a full trial is feasible and warranted to test the effectiveness of PIM versus NEMEX and standard education with the potential to provide mechanistic insights based on nervous system modulation.